ผลของโปรแกรมการสร้างความเข้มแข็งทางใจที่เน้นการฝึกสติ ต่อภาวะซึมเศร้าในผู้สูงอายุโรคซึมเศร้า - ปานทอง กันต์ฤทัย; แดงด้อมยุทธ์ เพ็ญนภา (วารสารพยาบาลเกื้อการุณย์, 2018)
Abstract The purposes of this quasi-experimental research were to compare: 1) depression in older persons with major depressive disorder before and after receiving the resilience quotient emphasizing mindfulness-based program, and 2) depression in older persons with major depressive disorder who received the resilience quotient emphasizing mindfulness-based program and those who received routine nursing care. The sample consisted of 34 older persons with major depressive disorder, who met the inclusion criteria and received services at the out-patient department. They were matched-pair by ages and depression scores. Research instruments comprised of: 1) The resilience quotient emphasizing mindfulness-based program, 2) Beck Depression Inventory scale. All instruments were verified for content validity by 5 professional experts. The reliability of Beck Depression Inventory scale was reported by Cronbach’s alpha as of .90. Data were analyzed using mean, standard deviation and t-test. Major findings were as follows: (1) the depression in older persons with major depressive disorder was significantly lower, at the .05 level, after receiving the resilience quotient emphasizing mindfulness-based program as compared to before receiving the program. (2) Depression in older persons with major depressive disorder who received the resilience quotient emphasizing mindfulness-based program was significantly lower than those who received routine nursing care at the .05 level.